The Role of Coretax System in Increasing the Influence of Tax Knowledge on the Quality of VAT Period Tax Return Information Through Taxpayer Compliance - Riyanto, Agung; Istikhoroh, Siti (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine the role of the Coretax System in strengthening the effect of tax knowledge on the quality of VAT Periodic Tax Return information, with taxpayer compliance as a mediating variable. This research is motivated by the growing need to understand how the implementation of an integrated digital tax system supports accuracy in tax reporting and compliance behavior within the Indonesian tax reform era. A quantitative explanatory approach was applied using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Data were collected through questionnaires distributed to 119 corporate taxpayers registered at KPP Pratama Gresik, using a five-point Likert scale. Validity and reliability testing showed AVE values above 0.50 and Cronbach’s Alpha above 0.70, confirming that all indicators were suitable for analysis. The findings indicate that tax knowledge has a significant positive effect on taxpayer compliance but does not directly influence information quality. Meanwhile, taxpayer compliance significantly improves the quality of VAT Periodic Tax Return information and fully mediates the effect of tax knowledge on information quality. The Coretax System also has a significant direct influence on information quality but does not moderate relationships among other variables. This study highlights that reliable fiscal information quality depends not only on technological systems but also on taxpayer knowledge and compliance behavior, offering important implications for strengthening tax literacy and optimizing digital tax governance.